Aesthetics in performance : formations of symbolic construction and experience - Hobart, Angela; Kapferer, Bruce (Berghahn Books, 2005)
"In various ways, the essays presented in this volume explore the structures and aesthetic possibilities of music, dance and dramatic representation in ritual and theatrical situations in a diversity of ethnographic contexts in Europe, the Americas, Africa and Asia." "Each essay enters into a discussion of the "logic" of aesthetic processes exploring their social and political and symbolic import. The aim is above all to explore the way artistic and aesthetic practices in performance produce and structure experience."--Jacket